Development of a digital module for planning and installation of the audio system subject in audio video engineering skills competency - Dian ismidiati Idil; Nurhikmah H; Abd. Haling (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
The development of digital module in Planning and Installation of Audio Systems Subject for grade XI at SMKN 10 Makassar aims: (1) to discover the description of the needs for digital module for planning and installation audio system subject at SMKN Negeri Makassar, (2) to design the product of digital module in planning and installation of audio system at SMKN 10 Makassar, and (3) to measure the level of validity, practicality, and effectiveness of digital module for planning and installation of audio system at SMKN 10 Makassar. This study is a Research and Development (R and D) type of research, using the development model ADDIE model, which consists of five stages, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The number of test subjects was two validators, subject teachers, and class IX students at SMK Negeri 10 Makassar. This research shows that the student's needs are met with the required qualifications. Digital modules are developed according to the needs of students and teachers using Canva and Microsoft. The results of expert validation, teacher responses, limited trials, and small group trials, as well as evaluation of student learning outcomes, are in the very good category, indicating that the digital module for planning and installing audio systems is declared valid and practical (easy to use) and effectively used in the learning process. AbstrakPengembangan modul digital pada Mata Pelajaran Perencanaan dan Instalasi Sistem Audio untuk kelas XI di SMK Negeri 10 Makassar bertujuan yaitu untuk: (1) mengetahui gambaran kebutuhan modul digital perencanaan dan instalasi sistem audio di SMK Negeri 10 Makassar, (2) mendesain produk modul digital perencanaan dan instalasi sistem audio di SMK Negeri 10 Makassar, (3) mengukur tingkat validitas, kepraktisan, dan efektifitas modul digital perencanaan dan instalasi sistem audio di SMK Negeri 10 Makassar. Penelitian ini merupakan penelitian jenis Research and Development (R and D) menggunakan model ADDIE terdiri dari lima tahapan yaitu: (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. Jumlah subjek uji coba yaitu 2 validator, guru mata pelajaran, dan peserta didik kelas IX SMK Negeri 10 Makassar. Hasil penelitian ini menunjukkan tingkat kebutuhan peserta didik berada pada kualifikasi dibutuhkan. Modul digital dikembangkan sesuai kebutuhan peserta didik dan guru dengan menggunakan canva dan Microsoft. Hasil validasi ahli, tanggapan guru, uji coba terbatas, dan uji coba kelompok kecil, serta evaluasi hasil belajar peserta didik berada pada kategori sangat baik sehingga menunjukkan bahwa modul digital perencanaan dan instalasi sistem audio dinyatakan valid dan praktis (mudah digunakan) dan efektif digunakan dalam proses pembelajaran.Kata Kunci: kreativitas dalam pembelajaran; modul digital; perencanaan dan instalasi sistem audio